2017
DOI: 10.1111/mmi.13722
|View full text |Cite
|
Sign up to set email alerts
|

Sfp1 and Rtg3 reciprocally modulate carbon source‐conditional stress adaptation in the pathogenic yeast Candida albicans

Abstract: SummaryThe pathogenicity of the clinically important yeast, Candida albicans, is dependent on robust responses to host‐imposed stresses. These stress responses have generally been dissected in vitro at 30°C on artificial growth media that do not mimic host niches. Yet host inputs, such as changes in carbon source or temperature, are known to affect C. albicans stress adaptation. Therefore, we performed screens to identify novel regulators that promote stress resistance during growth on a physiologically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 99 publications
(138 reference statements)
1
19
0
Order By: Relevance
“…921 and ORF19 . 4722 ) have been characterized elsewhere [ 30 33 ] but the fact that they also displayed a phenotype in our study validates the experimental model and screening approach. Another four deletion mutants ( zcf8 Δ/Δ [ orf19 .…”
Section: Resultssupporting
confidence: 82%
“…921 and ORF19 . 4722 ) have been characterized elsewhere [ 30 33 ] but the fact that they also displayed a phenotype in our study validates the experimental model and screening approach. Another four deletion mutants ( zcf8 Δ/Δ [ orf19 .…”
Section: Resultssupporting
confidence: 82%
“…Yet, there seem to be direct links to the regulators as well. For instance, other studies have implicated Rtg1/3 in some facets of C. albicans sugar metabolism (Dalal et al, 2016;Kastora et al, 2017). Likewise, full-genome chromatin immunoprecipitation experiments have shown that Rtg1p and Rtg3p bind upstream of a large, eclectic set of metabolismrelated genes (Pé rez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the UPR, ER proteins are involved in maintaining a favorable environment for protein folding. A zinc finger transcription factor, Sfp1p, responds to carbon-conditional stress and oxidative stress in C. albicans [92,93]. Mutants lacking SFP1 were found to be more resistant to oxidative radicals and macrophage killing [91].…”
Section: Protein Folding and Maturationmentioning
confidence: 99%
“…Mutants lacking SFP1 were found to be more resistant to oxidative radicals and macrophage killing [91]. Together with another transcription factor, Rtg3p, Sfp1p negatively regulates the transcription of stress response genes CAP1, CTA4, and HOG1 [89,[91][92][93][94]. Cap1p is a bZIP transcription factor that controls antioxidant gene expression and HOG1 encodes a transcription factor that activates a MAP-kinase cascade to result in resistance to oxidative stresses [91,92].…”
Section: Protein Folding and Maturationmentioning
confidence: 99%
See 1 more Smart Citation